Mediastinal Mass: A Diagnostic Odyssey from Iron Deficiency Anaemia to Thymoma - Leite, Ana Isabel Bento Ferreira; Mesquita, Gonçalo; Mandim, Andreia; Veiga, Luis; Oliveira, Raquel; Novo, Filipa; Campos, Anita (Brazilian Journal of Case Reports, 2025)
Thymic epithelial tumours represent a heterogeneous group of rare thoracic cancers. In adults, thymomas are the most common neoplasms arising in the thymus which is located in the anterior mediastinum. Mediastinal mass can be incidental findings on chest x-ray or present with systemic symptoms and/or direct effect of the mediastinal mass. The authors present the case of a 65-year woman with iron deficiency anaemia, hepatosplenomegaly, paravertebral node and mediastinal mass. Biopsy of the paravertebral node revealed extramedullary hematopoiesis (EMH). Biopsy of mediastinal mass revealed thymoma. She underwent video-assisted thoracoscopic surgery (VATS) thymectomy. The lesion was classified by the World Health Organization (WHO) system type B2 thymoma staging system of the tumor, node, metastasis (TNM) pT1a R0, Masaoka-Koga stage II. Three months later, thoracic computed tomography (CT) revealed a nodule inferior to the tumor site suspected of residual disease. The unexpected residual thymoma required treatment with radiotherapy. This case illustrates the difficulty of differentiating the etiology of anaemia. It highlights the current diagnostic approach to mediastinal mass.